Efecto del catalizador Generate sobre poblaciones microbianas de suelo, en arroz (Oryza sativa L.) bajo riego, en la zona de Babahoyo - Averos Alvarado, Lucio Gabriel (2017)
VIII. SUMMARY The present research work was carried out in the "La Rodríguez" Campus, belonging to the Febres Cordero Parish of the Babahoyo Canton. The objective was to evaluate the effect of the Generate catalyst on soil microbial populations, in rice (Oryza sativa L.), under irrigation, in the Babahoyo area. The sowing material used was INIAP FL-1480 rice variety, and the Generate Starter catalyst was evaluated in different doses, distributed in five treatments and four repetitions, using the experimental design of randomized complete blocks. The evaluation and comparison of means was determined with the Tukey test at 95% probability. The Generate Starter doses were applied 20 and 40 days after the transplant. The necessary cultural tasks were carried out for the adequate growth of the crop: irrigation, weed control, fertilization, phytosanitary control and harvest. The variables evaluated were plant height at 30 and 60 days, number of tillers, panicles per square meter, panicle length, number of grains per panicle, weight of a thousand grains, days to flowering, days to physiological maturation of the grain, microbiological analysis of soils, yield per hectare and economic analysis. The obtained results determined that the incorporations of the Generate catalyst in doses of 2.3 and 4 L / ha, affected the increase of the level of cellulolytic microorganisms in the soil. With the applications of Generate in doses of 5 L / ha, there was a population increase of Bacteria in the soil. A population increase of FBN in the soil was achieved with the application of Generate in a dose of 2 L / ha. The variables number of panicles per square meter, and days at flowering did not show significant statistical differences. The application of Generate in a dose of 5 L / ha, allowed the plants to achieve a good development, stimulating a greater increase in plant height. The highest values of number of panicles in square meter panicle length, number of grains per panicle, and weight of 1000 grains, were obtained with the application of Generate in a dose of 3 L / ha. The highest production and the highest net profit were achieved with the incorporation of Generate in a dose of 3 L / ha with 7414,25 kg / ha and $ 1064,28.